Tensiones en una prótesis parcial fija unitaria implantosoportada en primer premolar inferior con diferentes materiales mediante elementos finitos - Méndez , A. (2023)
AIM: To analyze stress in a metal-ceramic, zirconia and lithium disilicate implant-supported unitary fixed partial prosthesis in the first lower premolar through finite element analysis at a 500 N force. MATERIALS AND METHODS: Three study models were carried out, metalceramic, lithium disilicate and zirconium implant-supported crowns in the first lower premolar.The dental implant was made of titanium grade 5 based on the Bolt® model of UniDentalDirect with internal grooved connection (18 grooves) and the implant had a size of 11,0 x 4,5 mm, preformed abutment and integrated screw. The three designs had vertical and oblique (45°) forces applications at 500 N. The geometric modeling was performed with the SolidWorks® 2017 program and the results were obtained through the Von mises analysis using the CosmoWorks®2017 program. RESULTS: The lowest value of maximum stress on crown level, under vertical and oblique forces, was found in the lithium disilicate crown with 21,9 MPa and 33,2 MPa, and with a minimum difference with the zirconium crown with 22,1 MPa and 35,1 MPa; on the abutment level, the zirconium crown had the lowest value of maximum stress with 18,6 MPa and 28,1 MPa; at the screw level, there were no significant differences. CONCLUSION: Metalceramic, lithium disilicate, and zirconia crowns proved to be materials of good compressive and tensile strength, but it was concluded that the zirconia crown design generated lower overall stress.